A Note on the Generalized 𝑞-Bernoulli Measures with Weight 𝛼 - T. Kim; S. H. Lee; D. V. Dolgy; C. S. Ryoo (Abstract and Applied Analysis)
We discuss a new concept of the 𝑞-extension of Bernoulli measure. From those measures, we derive some interesting properties on the generalized 𝑞-Bernoulli numbers with weight 𝛼 attached to 𝜒.